2017
DOI: 10.3892/ol.2017.6337
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid-type fibromatosis of the breast: A report of 2 cases

Abstract: Mammary fibromatosis is a rare and locally aggressive benign tumor of the breast; it originates from fibroblasts and myofibroblasts within the breast parenchyma and does not metastasize. The condition is locally aggressive and has a high rate of recurrence. The etiology of mammary fibromatosis is unknown. Breast imaging examinations are not specific for fibromatosis and often imitate breast cancer. The current study presents 2 cases of women with breast fibromatosis, the first of which exhibited a locally adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Desmoid tumor or desmoid-type fibromatosis is an entity of unknown etiology, defined by the World Health Organization (WHO) as ''clonal fibroblastic proliferation arising in the deep soft tissues, with a tendency to infiltrate local tissues and locally recur, but an inability to metastasize'' (1,8,9). Desmoid-type fibromatosis usually presents in the age range of 15-60 years and is more than twice as common in women (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desmoid tumor or desmoid-type fibromatosis is an entity of unknown etiology, defined by the World Health Organization (WHO) as ''clonal fibroblastic proliferation arising in the deep soft tissues, with a tendency to infiltrate local tissues and locally recur, but an inability to metastasize'' (1,8,9). Desmoid-type fibromatosis usually presents in the age range of 15-60 years and is more than twice as common in women (8).…”
Section: Discussionmentioning
confidence: 99%
“…Desmoid tumor (synonym: desmoid-type fibromatosis) is a benign lesion of the connective tissue with a tendency to infiltrate adjacent tissue but without metastatic potential. Development in the breast is very rare (1)(2)(3)(4). Desmoid of the breast represents a diagnostic challenge because the lesions mimic breast carcinoma radiologically (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…On IHC, fibromatosis stains positively for β-catenin, SMA, and vimentin; variably for desmin and estrogen receptor (ER), and negatively for CD34, p63, and pankeratins. Patients who have familial adenomatous polyposis demonstrate mutations of the APC gene, while sporadic cases may show mutations of the CTNNB1 gene [1, 8, 13]. …”
Section: Bland Spindle Cell Lesionsmentioning
confidence: 99%
“…DT is characterized by local aggressiveness with a 20% -30% local recurrence rate, but without metastasis [1] [2]. In a previous study, the median age of patients was reported to be 12.2 years; 49% of patients were male, and 51% were female [3].…”
Section: Introductionmentioning
confidence: 99%
“…Desmoid tumor (DT) is defined as a borderline lesion of the connective tissue with a tendency to infiltrate adjacent tissue, but without metastatic potential, according to the World Health Organization's classification [1]. DT is characterized by local aggressiveness with a 20% -30% local recurrence rate, but without metastasis [1] [2].…”
Section: Introductionmentioning
confidence: 99%